Public expenditures transferring and its role in the redistribution of income with particular reference to the experiences of elected - جاسم محمد علي; عبد كاظم جابر (Journal of Economics and Administrative Sciences, 2015)
After the success of the reforms Keynesian save the capitalist system from collapse and to apply the concepts of state intervention in economic activity in order to revive aggregate demand to achieve the purposes of macro-economic policies which draw their scope of economic (John Keynes) theory of effective demand, which created the new role of the state away from the classical concepts. Valley transmission role of the State of (State Guardian) to the process of state overlapping that increased and social functions have become responsible for raising the standard of living of classes with limited incomes, in particular, and the rest of the classes in general, through the expansion of the delivery of public services, including the costs of manufacturing the social face of disease, disability and aging and unemployment. Has expanded the size of these expenses in the Iraqi economy after 2003 as a result of the requirements of the process of economic justice have been through parliamentary legislation to establish a number of ministries, agencies, and institutions such as the Ministry of Human Rights and the Ministry of Displacement and Migration and the issue, justice and institutions of the martyrs and political prisoners in order to achieve social balance and achieve social justice in Iraqi society. Became the state is responsible for the fight against economic and social underdevelopment by creating the necessary capital and customizations to achieve adequate placed economic and social development and restoring the balance between community groups. And expenses Manufacturing government are subject to factors outside the scope of economic analysis, such as political factors and ideology that relate to spending on social services and used government authority Finance to maintain its control over the state, either through tax policy or through public expenditure, as happened during the Great Depression of the world for the period (1929 - 1933), which increased unemployment that has become there armies of the unemployed, the hungry and the coup that threatened the capitalist system and its termination as a state